2020
DOI: 10.1161/jaha.119.014375
|View full text |Cite
|
Sign up to set email alerts
|

Role of Vascular Adaptation in Determining Systolic Blood Pressure in Young Adults

Abstract: Background Two individuals can have a similar pulse pressure ( PP ) but different levels of systolic blood pressure ( SBP ), although the underlying mechanisms have not been described. We hypothesized that, for a given level of PP , differences in SBP relate to peripheral vascular resistance ( PVR ); and we tested this hypothesis in a large cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Many investigators and physicians hold the view that, from the perspective of pathophysiology, ISH in young people is caused by the increased pulse pressure amplification, which is believed to be related to the high elasticity of arteries, and thus ISH is a benign status [4]. Contrarily, other investigators revealed that ISH in the young is caused by increased stroke volume and arterial stiffness [5] and vascular maladaptation [6]; from this perspective view of point, ISH is not benign. Importantly, many data exploring the long-term cardiovascular risk of young people with ISH from large cohorts were published recently and demonstrated that ISH in young people is significantly associated with increased risk of cardiovascular events and mortality in their later life [7,8].…”
mentioning
confidence: 99%
“…Many investigators and physicians hold the view that, from the perspective of pathophysiology, ISH in young people is caused by the increased pulse pressure amplification, which is believed to be related to the high elasticity of arteries, and thus ISH is a benign status [4]. Contrarily, other investigators revealed that ISH in the young is caused by increased stroke volume and arterial stiffness [5] and vascular maladaptation [6]; from this perspective view of point, ISH is not benign. Importantly, many data exploring the long-term cardiovascular risk of young people with ISH from large cohorts were published recently and demonstrated that ISH in young people is significantly associated with increased risk of cardiovascular events and mortality in their later life [7,8].…”
mentioning
confidence: 99%
“…In hypertension, the elevation in BP is mostly driven by increases in PVR [33]. It is also known that smaller diameter arteries contribute more to the mediation of PVR relative to larger diameter arteries such as the aorta, which mainly serves a conduit function [34].…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation is the potential impact of arterial compliance and peripheral vascular resistance on SBP measurements [22]. Age-related vascular changes and arterial stiffness could affect the accuracy of non-invasive measurements, leading to differences between ClearSight finger cuff arterial pressure and intra-arterial pressure [23]. Additionally, the finger cuff technology itself may have limitations in accurately capturing rapid changes in SBP [24].…”
Section: Discussionmentioning
confidence: 99%